2007
DOI: 10.1148/rg.271065080
|View full text |Cite
|
Sign up to set email alerts
|

Bowel Hot Spots at PET-CT

Abstract: Positron emission tomography (PET) with 2-[fluorine-18]fluoro-2-deoxy-d-glucose (FDG) has been shown to be sensitive in the detection of many bowel malignancies, but its specificity is lower because of various physiologic and pathologic patterns of bowel FDG uptake. PET-computed tomography (CT) can be useful in localizing and characterizing foci of increased FDG uptake within the bowel. As the use of PET-CT in the staging and monitoring of oncologic disease continues to expand, familiarity with these patterns … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
64
0
2

Year Published

2008
2008
2023
2023

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 110 publications
(66 citation statements)
references
References 34 publications
0
64
0
2
Order By: Relevance
“…It is confirmed that PET activity correlated well with active inflammation in both UC and CD, suggesting that this may be a noninvasive method of identifying disease activity in patients with IBD [66] . Neurath et al suggested that FDG-PET appear to be a reliable noninvasive tool for simultaneous detection of inflamed areas in the small and large bowel of patients with CD and can be used to detect disease activity in the terminal ileum and colon of CD patients with high sensitivity and specificity [67] .…”
mentioning
confidence: 64%
“…It is confirmed that PET activity correlated well with active inflammation in both UC and CD, suggesting that this may be a noninvasive method of identifying disease activity in patients with IBD [66] . Neurath et al suggested that FDG-PET appear to be a reliable noninvasive tool for simultaneous detection of inflamed areas in the small and large bowel of patients with CD and can be used to detect disease activity in the terminal ileum and colon of CD patients with high sensitivity and specificity [67] .…”
mentioning
confidence: 64%
“…CT enterography usually uses negative oral contrast material that causes bowel distention without increasing CT attenuation and helps avoid the potential PET attenuation artifacts that can be seen with high-density barium-or iodinebased oral contrast material. Also, the bowel distension obtained by CT enterography reduces background 18 F-FDG activity and physiologic uptake of 18 F-FDG in the bowel, allowing better definition of uptake in the bowel wall (14)(15)(16).…”
Section: Discussionmentioning
confidence: 99%
“…This method permits to obtain a distension of the bowel and an optimal evaluation of the wall thickening. There are also some negative oral contrast media commercially available (7)(8)(9)(10).…”
Section: Petandlbdmentioning
confidence: 99%